The Relationship Between Lactation Period and Colostrum Age With Colostrum Protein Content of Friesian Holstein (FH) Dairy Cattle in KPSP Setia Kawan, Pasuruan District - Puspitasari, Tantri; Surjowardojo, Puguh; Rifa'i, Rifa'i (Universitas Veteran Bangun Nusantara, 2023)
Colostrum is the secretion of the udder glands after the cow gives birth and is given to the calf for 3-5 days. The purpose of this study was to determine the relationship between the lactation period and colostrum age on the colostrum protein content of FH dairy cows. This research was conducted at KPSP Setia Kawan, Pasuruan. The research was conducted in August-November 2022. The research materials were FH dairy cows with lactation periods 1,2,3, and cow colostrum which were analyzed with the Lactoscan Milk Analyzer. The research method uses case study method and purposive sampling. Research using simple linear regression analysis and correlation. The results of the regression equation study the relationship between the lactation period and colostrum protein content, namely Y =5.22+0.46X with a correlation value (r)=0.158 and a coefficient of determination (R2)=0.025. The results of the regression equation for the relationship between colostrum age and colosrum protein content are Y=10.79-1.55X with a correlation value (r)=0.88 and a coefficient of determination (R2)=0.77. The conclusion of the study is that there is a positive relationship between the lactation period and colostrum protein and there is a negative relationship between colostrum age and colostrum protein. Keywords : FH dairy cattle, colostrum, lactation period, colostrum protein.